2016
DOI: 10.3389/fmicb.2016.00242
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and In Vivo Evaluation: Photodynamic Antibacterial Chemotherapy of Lysine-Porphyrin Conjugate

Abstract: Lysine-porphyrin conjugate 4i has potent photosensitive antibacterial effect on clinical isolated bacterial strains such as Methicillin-resistant Staphylococcus aureus (MRSA), Escherichia coli, and Pseudomonas aeruginosa. The mechanism of photodynamic antibacterial chemotherapy of 4i (4i-PACT) in vitro and the treatment effect in vivo was investigated in this paper. Atomic force microscopy (AFM) revealed that 4i-PACT can effectively destroy membrane and wall of bacteria, resulting in leakage of its content. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 42 publications
2
52
1
Order By: Relevance
“…The images stained by PI verified the antibacterial activity by carbazole derivatives BMEPC and BMEMC. Compared with the previously reported photosensitizers, 33 , 34 the MIC value of BMEPC is relatively lower under irradiation, indicating a more prominent effect on bacterial inhibition. These results suggest that photoinduced active species are the dominant factors to kill bacteria.…”
Section: Resultscontrasting
confidence: 72%
“…The images stained by PI verified the antibacterial activity by carbazole derivatives BMEPC and BMEMC. Compared with the previously reported photosensitizers, 33 , 34 the MIC value of BMEPC is relatively lower under irradiation, indicating a more prominent effect on bacterial inhibition. These results suggest that photoinduced active species are the dominant factors to kill bacteria.…”
Section: Resultscontrasting
confidence: 72%
“…The wound healing rate decreased in the order of 100 μM > 200 μM > 50 μM, which parallels the order of the bactericidal effect. This suggests that PPIX-ED-PACT accelerates wound healing via bactericidal effects against P. aeruginosa [22,27,33]. The CFUs of P. aeruginosa in the wound and the wound healing rate in vivo revealed that PPIX-ED-PACT is efficient in the treatment of bacterial infection, and the therapeutic effect of PPIX-ED was better at 100 μM than at 50 or 200 μM.…”
Section: Plos Onementioning
confidence: 91%
“…The photodynamic effects of different photosensitizers on P. aeruginosa have been demonstrated [20][21][22][23]. In vivo, PACT has been primarily used to improve wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism is based on the photochemical reactions of photosensitizers (PSs). Upon irradiation with light whose wavelength matches the absorption of the PSs, hydroxyl radicals, superoxides, or singlet oxygen ( 1 O 2 ) can be generated, causing damage to cell membranes and DNA molecules …”
Section: Nanomaterials For Antibiotic‐free Antibacterial Applicationsmentioning
confidence: 99%